Through-life integration using PLM - Gomez, M.; Baxter, David; Roy, Rajkumar; Kalta, M. (Cranfield University, 2009)
It is widely agreed that organisations would benefit from a PLM implementation founded on a standard structure that integrates through-life information and knowledge. Thus, this paper describes a PLM data structure that provides a standard repository of data through all the stages of the lifecycle: conception, manufacture, and operation. This structure classifies the data into project, product, process and resource, and has been implemented into the PDM system Teamcenter Engineering as part of a case study with a vacuum pump manufacturer. A methodology to implement a knowledge structure from an ontology editor into PDM system is also presented.
Organised by: Cranfield University
Keywords: Product Lifecycle Management; PLM; data structure; design; manufacturing; service; knowledge